The Holy month of Ramadan: A blessed union (Etihad) of societal collective effervescence, belonging and positive mental health for all [version 1; peer review: 2 approved] - Mohammed Baqer Habeeb Abd Ali; Abdulla Yoqoub AlHammadi; Sultan Abdullah Mohammed Alshaer; Sindya Saif Almarzrouei; Sarah Sanad; Maryam Butti Saeed Alshamsi; Alounoud Almarzooqi; Mini Abraham; Sadeq AL-Fayyadh; Richard Mottershead; Ghada Shahrour; John Hall; et al. (F1000Research)
Ramadan is a month-long religious festival and observed globally by Muslims, characterised by intermittent fasting, prayer, reflection and a focus on community. Fasting is one of the five pillars of Islam and has well documented positive impacts on physical health. An article by Bandarian et al., (2021) highlighted the research gaps in Ramadan fasting studies relating to health and disease. The article called for more research studies on different health and disease conditions other than nutrition and metabolic disorders. The authors on this correspondence article continue this call and respectfully articulate the wider societal impact and benefits of Ramadan through its positive impact, through embracing multicultural, multinational and multifaith communities within the United Arab Emirates.